Sustainable Soil Water Management Systems - Basch, G. (2012)
Soil quality and its management must be considered as key elements for an effective management of water resources, given that the hydrological cycle and land management are intimately linked (Bossio et al. 2007). Soil degradation has been described by Bossio et al. (2010) as the starting point of a negative cycle of soil-water relationships, creating a positive, self-accelerating feedback loop with important negative impacts on water cycling and water productivity. Therefore, sustainable soil management corresponds to sustainable water management through the improvement of soil water management. The purpose of this chapter is to review the existing options of soil water management systems and their potential contribution to the improvement of available soil water in the root zone, water use efficiency and water productivity. Ultimately, these water-related aspects seem to be the only solution to producing enough food, feed, fiber and biofuels for 1.5 times today‘s world population, without competing excessively with the existing natural ecosystems and their services and the water resources allocated to them and to other human activities.